2023
DOI: 10.3390/biom13030427
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Verbascum sinuatum L.: Health Benefits and Potential as New Ingredients for Industrial Applications

Abstract: Verbascum sinuatum (V. sinuatum) is a plant belonging to the Scrophulariaceae family that has been used as an ingredient in traditional medicine infusions for the treatment of many diseases. The aerial part of this plant is a source of bioactive compounds, especially polyphenols and iridoids. Moreover, antioxidant activity studies have shown that V. sinuatum phenolic and flavonoid composition is higher than those in other plants of the same genus. V. sinuatum bioactive compound composition could vary according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…This confirmed that F. betulina, Verbascum L., and U. tomentosa extracts were seen to be more active against viral particles than Achillea millefolium L., Hippophae rham-noides L., and Hypericum L. extracts. Verbascum L. exhibits antiviral properties [40,41] and its alcoholic extracts have even been used in therapy, improving the health of patients with COVID-19. Additionally, F. betulina and U. tomentosa extracts were also mentioned as antiviral materials [42][43][44].…”
Section: )mentioning
confidence: 99%
“…This confirmed that F. betulina, Verbascum L., and U. tomentosa extracts were seen to be more active against viral particles than Achillea millefolium L., Hippophae rham-noides L., and Hypericum L. extracts. Verbascum L. exhibits antiviral properties [40,41] and its alcoholic extracts have even been used in therapy, improving the health of patients with COVID-19. Additionally, F. betulina and U. tomentosa extracts were also mentioned as antiviral materials [42][43][44].…”
Section: )mentioning
confidence: 99%
“…Chemically, Verbascum plants are characterized by the presence of iridoid and neolignan type glycosides, oleanan type terpenes, flavonoids, polysaccharides, saponins, steroids and alkaloids ( Küçük et al, 2016 ; Blanco-Salas et al, 2021 ; Zengin et al, 2021 ; Zengin et al, 2023 ). They possessed versatile biological properties such as antioxidant, cytotoxic, antimicrobial and anti-inflammatory activities ( Tatli and Akdemir, 2006a ; Kahraman et al, 2012 ; Blanco-Salas et al, 2021 ; Donn et al, 2023 ). Moreover, bioactives of Verbascum species, including apigenin, verbascoside and chlorogenic acid were found to possess antioxidant, anticancer, anti-Alzheimer activities ( Bender et al, 2021 ; Zengin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important that Verbascum L. has also been found to have antiviral properties. Its aqueous and alcoholic extracts have been used in therapy, improving the prognosis of persons with COVID-19 [12,13]. Birch polypore (Fomitopsis betulina) is an edible, medicinal mushroom (when young).…”
Section: Introductionmentioning
confidence: 99%
“…As an assumption [9,10,26], it might be predicted that the introduction of ZnO nanoparticles into the F. betulina, Verbascum L. or U. tomentosa extracts (separately) might lead to antifungal and antiviral activity of the layers on the packaging material surfaces. The coatings containing zinc oxide nanoparticles as an additive will be UV resistant due to their UV-shielding properties, and they will maintain the plant extracts' active compound effectiveness [12,[16][17][18][19][20]. As a conclusion [4][5][6], to analyze the antifungal properties of the coatings' selected strains, Candida albicans PCM 2566 and Fusarium oxysporum CCM F-545 were used.…”
Section: Introductionmentioning
confidence: 99%